Stress analyses of compound cylinders with interlayer pressure after autofrettage. (June 2018) - Zhao, Mengjun; Wu, Zhilin; Cai, Hongmin
Abstract: In this paper, the compound cylinder technique with interlayer pressure after autofrettage (IPA) is introduced to enhance the bearing capacity of cylinders. Theoretical analyses show that IPA technique may make the elastic-limit bearing pressure of cylinders approach to 1.5 times of the yield strength σ s ; and then further optimum calculation under the given working pressure of the p w = 1.07 σ s reveals that the cylinders of different radius ratios with IPA can be kept in elastic state, besides the minimum total radius ratio r o /r i is approximately equal to 3.29. Subsequently both analytical calculation and finite element analyses on the compound cylinder with the total radius ratio of the 3.29, show that no yielding happen in autofrettage process and working loading stage. These results suggest that the compound cylinder with IPA is a favorable method to increase the elastic-limit bearing pressure of cylinders; in addition, by the optimum calculation methods used in this paper, the minimum total radius ratio r o /r i under any given working pressure can be calculated out. Highlights: In this paper, the compound cylinder technique with interlayer pressure after autofrettage (IPA) is introduced to enhance the bearing capacity of cylinders. Theoretical analyses show that IPA technique may make the elastic-limit bearing pressure of cylinders approach to 1.5 times of the yield strength σ s ; and then further optimum calculation under the given working pressure of the p w = 1.07 σ s reveals that the cylinders of different radius ratios with IPA can be kept in elastic state, besides the minimum total radius ratio r o /r i is approximately equal to 3.29. . Subsequently both analytical calculation and finite element analyses on the compound cylinder with the total radius ratio of the 3.29, show that no yielding happen in autofrettage process and working loading stage. . These results suggest that the compound cylinder with IPA is a favorable method to increase the elastic-limit bearing pressure of cylinders; in addition, by the optimum calculation methods used in this paper, the minimum total radius ratio r o /r i under any given working pressure can be calculated out.